OC-066 Economic and quality-of-life burden of moderate-to-severe irritable bowel syndrome with constipation (ibs-c) in the uk: the ibis-c study. (22nd June 2015) - Yiannakou, Y; Eugenicos, M; Sanders, DS; Emmanuel, A; Whorwell, P; Butt, F; Bridger, S; Arebi, N; Millar, A; Kaushik, V; Rance, M; Mackinnon, J; et al.
Abstract : Introduction: This is the first study to assess the burden of IBS-C in 6 European countries (France, Germany, Italy, Spain, Sweden, UK). Here we present the results for the UK. Method: Observational, retrospective-prospective (6 months each) study in patients (pts) diagnosed with IBS-C in the last five years (Rome-III criteria) and moderate-to-severe symptoms at baseline: IBS-Symptom Severity Score (IBS-SSS) ≥175. Health resource utilisation was retrospectively and prospectively assessed. Symptom evolution was assessed in the prospective period, and quality-of-life (QoL) was assessed at baseline with EuroQoL-5D (EQ-5D) and IBS-QoL. Work productivity was prospectively assessed using the Work Productivity and Activity Impairment (WPAI): IBS-C questionnaire. Results: 104 pts were included (79% severe, mean age [± SD] 45.5 ± 14.6 yrs, 93% female). At baseline, symptom severity (IBS-SSS; severe >300) was 373.1 ± 82.5; presenteeism (WPAI:IBS-C; mean ± SD): 47.9% ± 28.7%; absenteeism: 8.4% ± 24.2%; work productivity loss: 51.5% ± 27.2%; daily activity impairment: 56.8% ± 29.6%. Mean IBS-QoL was 57.2 ± 24.2, (scale: 0–100 [best-to-worst]) and mean EQ-5D was 54.0 ± 23.3 (scale: 0–100 [worst-to-best]. 87.5% and 64.4% of pts reported moderate-to-severe problems in pain/discomfort, anxiety/depression respectively. Most prevalent symptoms were abdominal pain (92%) and bloating (91%). 70% pts consulted a GP, and 100% a gastroenterologist; mean: 6.2 and 2.7 visits, respectively. 24% pts required emergency department visits or hospitalisation (mean stay [95% CI]: 12 [2.5–21.1] days). 52% had a diagnostic test (mean [95% CI]: 3.6 [2.9–4.4]). 90% pts took prescription drugs for IBS-C. Mean (95% CI) annual direct cost for the NHS: £ 1753 (1251–2308); the mean pt cost: £ 315 (184–482). 51% of pts took sick leave (mean: 5.2 times; mean duration: 26 days) and 82% had productivity losses (mean: 162 h). Mean indirect costs were £ 3407 (2078–4977). Total costs amounted to £ 5443 (3970–7252)/year. Conclusion: Moderate-to-severe IBS-C has a major impact on patient QoL, productivity, and healthcare resource utilisation. Disclosure of interest: Y. Yiannakou Conflict with: Grants: Shire; Medtronic. Speaker fees: Almirall; Shire; Sucampo, M. Eugenicos Conflict with: Consultant/Advisory Board Member: Almirall; Astellas; Dr Falk Pharma; NAPP; and Shire, D. Sanders Consultant for: Almirall, A. Emmanuel Conflict with: Advisory Board and Educational Talk honoraria: Almirall., P. Whorwell Conflict with: Consultant/research grant support: Almirall; Chr. Hansen; Danone Research; Ironwood; Salix; Shire; Sucampo, F. Butt: None Declared, S. Bridger: None Declared, N. Arebi: None Declared, A. Millar Conflict with: The hospital received payment from Almirall for the conduct of the study, V. Kaushik Conflict with: Advisory Board and Educational Talk honoraria: Almirall. Meeting support: Cooks; Tillotts; AbbVie., M. Rance Employee of: Almirall, J. Mackinnon Employee of: TFS Develop S. L., contracted by Almirall S. A to conduct the study, J. Bertsch Employee of: TFS Develop S. L, contracted by Almirall S. A. to conduct the study, J. Fortea Employee of: Almirall, J. Tack Conflict with: Grants/research support: Abbott; Novartis; Shire. Honoraria/consultancy fees: Almirall; AstraZeneca; Danone; GI Dyamics; GlaxoSmithKline; Ironwood; Janssen; Menarini; Novartis; Rhythm; Shire; Takeda; Theravance; Tsumura; Will Pharma; Zeria. Speaker fees: Abbott; Almirall; AstraZeneca; Janssen; Menarini; Novartis; Shire; Takeda; Zeria.